IMPACT OF PSYCHOLOGICAL OWNERSHIP ON INNOVATION AND GROWTH IN INDONESIA BUSINESS FIRMS - Santoso, Adi (International Journal of Psychosocial Rehabilitation, 2020)
For long-run success, both innovation and growth are the keys. However, the role of psychological ownership in the recent years is less observed both in theoretical and empirical context. This study aims to analyze the effect of psychological ownership on innovation and growth opportunities in Indonesia. Different measuring items for both dependent and independent variables were added in the questionnaire and employees from different business firms were selected as a sample of interest. descriptive analysis, correlation analysis and regression analysis have been performed and results shows that there is a significant relationship among range of psychological factors, innovation, and business growth opportunities. However, this research is limited in different context. For instance, advanced structural model like SEM is not applied, missing with the demographic details. The findings of present study is of great support for industry experts, business owners, and market analysts for exploring the relationship among the targeted variables. Additionally, this study has contributed in the field of business psychology.